PBL: rethinking chemistry laboratories - M. F. Cañas Cano (Universitat Politècnica de València, 2019)
A Chemistry learning involves theory and practice in the laboratory, we expect to achieve significant learning, however, we do not get this goal. In our university, General Chemistry is based on Problem Based Learning (PBL) and, the laboratory practice ́s has a green approach. The students do and analyse why they do. When we give them a guide, they follow "the recipe" and don ́t have opportunities  to do research and make decisions, more according to PBL methodology. Since 2016each group of students propose their own laboratory practice. They have permanent  eedback for reorienting their proposal. The data collected was qualitative. It involved  observation, analysis of the student's perception and their product. It conducted to preliminary conclusions, respect for teamwork, self-learning, and oral writing communication.